PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN COOPERATIVE LEARNING TIPE JIGSAW DI KELAS IV SDN 01 PAYAKUMBUH BALAI GADANG - SAPUTRA, KURNIAWAN ADE EKA (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
Abstrack This research aimed to describe the improving of students achievement in sains learning by using Type Cooperative Learning Tipe Jigsaw at grade IV SDN 01 Payakumbuh Balai Gadang. The kind of this research is an action research with quantitative and qualitative approach. The assessment of lesson pane at the first cycle was  81,85 % it increased 92,85 % at second cycle. The score of teacher activity at the first cycle was 79,45 % it increased 95,45 %. The score of students activity at the first cycle was 68,75 % it increased 90,15% at the second cycle. The student achievement improved from 75,5 at cycle I to 85,82 at cycle II. It can be concluded that Type Cooperative Learning Tipe Jigsaw increase the students learning achievement in sains at grade IV SDN 01 Payakumbuh Balai Gadang. Kata Kunci:hasil belajar; IPS; Cooperative Learning Tipe Jigsaw)